2020
DOI: 10.1186/s12884-020-03283-2
|View full text |Cite
|
Sign up to set email alerts
|

Women’s perceptions of COVID-19 and their healthcare experiences: a qualitative thematic analysis of a national survey of pregnant women in the United Kingdom

Abstract: Background The aim of this national survey was to explore pregnant women’s perceptions of COVID-19 and their healthcare experiences. Methods Through patient and public involvement, a questionnaire was developed and advertised via the BBC website, Twitter and other online media during May 2020. The findings were analysed by qualitative thematic analysis. Women who are currently pregnant, or who have delivered during the COVID-19 pandemic were invited to partake in a national online survey. Results One thous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
205
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(238 citation statements)
references
References 8 publications
14
205
1
11
Order By: Relevance
“…The media has been reported to play a significant part in perception of hospitals and ‘risk of death’ during the COVID-19 pandemic in women’s maternity care; a qualitative study evaluating perceived barriers to care for pregnant women found barriers present due to changes in the way services were delivered, virtual consultations and different perceived thresholds for seeking help. 18 Where caregivers had received adequate health education and signposting to decision-making tools antenatally, they felt empowered to seek help without delay.…”
Section: Discussionmentioning
confidence: 99%
“…The media has been reported to play a significant part in perception of hospitals and ‘risk of death’ during the COVID-19 pandemic in women’s maternity care; a qualitative study evaluating perceived barriers to care for pregnant women found barriers present due to changes in the way services were delivered, virtual consultations and different perceived thresholds for seeking help. 18 Where caregivers had received adequate health education and signposting to decision-making tools antenatally, they felt empowered to seek help without delay.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty about the best treatment and clinical management of patients with COVID-19 may affect the mind and psyche of pregnant women, with implications for their health care experiences [ 25 ]. Depression and anxiety are associated, and both can occur due to the COVID-19 pandemic [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high overall score indicates a high level of anxiety. Anxiety levels are defined according to the total score as follows: minimal anxiety (0-7), mild anxiety (8)(9)(10)(11)(12)(13)(14)(15), moderate anxiety (16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and severe anxiety (26-63) [17]. A validated Brazilian Portuguese version of the BAI with adequate internal consistency (0.88-0.92) was used in this study [18,19].…”
Section: Questionnaires' Applicationmentioning
confidence: 99%
“…There have also been changes in the procedures for screening for fetal growth restriction and gestational diabetes [ 48 , 49 ]. In the UK women have expressed anxiety about the changes to antenatal and intrapartum services [ 50 ]. These changes were thought to be barriers to diagnosing maternal or fetal abnormalities, possibly contributing to a rise in adverse outcomes.…”
Section: Effect Of Covid-19 On Pregancy Outcomesmentioning
confidence: 99%